Analysis of Sales Growth on Share Prices of South Korea Hybe Corporation Entertainment Companies - Santi Nurul Adha; Muhammad Sugiharto (Sean Institute, 2024)
This research aims to find out how sales growth and its influence on South Korean stock prices. The problem that occurred in this research was unstable and declining sales growth. This research was conducted at an entertainment company in South Korea, namely Hybe Corporation in 2020-2023. The analysis method in this research uses simple linear regression analysis with the help of Eviews 12 software. The results of the regression analysis test show that sales growth has no significant effect on stock prices, while for testing the coefficient of determination the results obtained are 0.218 or 21.8%, the sales growth variable is only can influence share prices by 21.8% and the remaining 78.2% is influenced by other variables not examined in this research. Further analysis regarding sales growth is one of the causes of increased sales growth in 2021, namely sales income from concerts which increased drastically by 883%, while the factor causing the decline in sales growth in 2023 is a decrease in income from advertising by -12.3% , Merchandise at -17.7% and content at -15.1%.